Study on the Applicability of Neutron Radiation Damage Method Used for High-Temperature Superconducting Tape Based on Geant4 and SRIM - Ying Zheng; Jinxing Zheng; Xudong Wang (Science and Technology of Nuclear Installations)
High-temperature superconducting material is a promising candidate to fabricate superconducting magnet for magnetic confinement fusion reactors. The DPA number of the 1 µm thick superconducting layer in a high temperature superconducting tape under neutron irradiation needs to be calculated to predict the property changes. The DPA cross sections, which ignore the spatial distribution of vacancies caused by PKAs, are commonly used to obtain the results of the damage energy and DPA. However, for geometric models with the thickness as small as 1 µm, the energy and angular distribution of PKAs reveal that a significant number of PKAs with relatively high energy tend to scatter forward and cross the boundary of model, so the thickness of model has the potential to affect the number of displaced atoms. In this paper, we developed a method based on Geant4 and SRIM to evaluate the deviation of the traditional analytic method caused by the thickness. Geant4 is used to obtain the location, direction, and energy of PKAs, while SRIM is used to track every PKA and obtain damage energy and the number of displaced atoms. The radiation damage calculation of simple thin plate models with different thicknesses and the tape model are conducted with the neutron energies from 1 to 14 MeV. The results show that PKAs need to be tracked continuously for models with thickness less than 10 µm and the deviation of the analytic formulas increases rapidly with the decrease of thickness. For the superconducting layer composed of four different elements in the tape, the deviation also depends on the proportion of each atomic species and the neutron-atom interaction cross sections under different incident neutron energy.